Преимущества и перспективы развития микроволновых распределительных сетей на основе технологий МИТРИС и DOCSIS - Нарытник, Т. Н.; Ксензенко, П. Я.; Химич, П. В. (Проблеми телекомунікацій, 2012)
Current trends of wireless backhaul networks development are presented in article and advantages from wireless access technology use in the microwave range are considered. It is shown that the decisive factor promoting more widespread introduction of the microwave backhaul networks is the increase in their capacity both in the direct and return channels therefore microwave networks start getting into that area which was occupied earlier undivided by decisions on the basis of an optical fibre. Tandem creation on the basis of MITRIS and DOCSIS technologies allows to making break in the field of microwave backhaul networks. Prospects of their further development in respect of increase in a network capacity as a whole and progressing increase in capacity of the return channel in particular which follow from alleged further improvement of the DOCSIS standard are specified also. Thus the increase in capacity becomes possible thanks to application of the channel bonding method and at the expense of CMTS architecture improvement in the modular construction direction higher flexibility and reliability of system as a whole is reached. As a result of the conducted researches the advantages which are a consequence of modular CMTS creation which are most distinctly shown when using CMTS DOCSIS together with the radio access equipment on the basis of the MITRIS domestic technology are established. Thus experience of the MITRIS technology application at creation of the MAN networks may to be use fully.
Keywords: распределительная сеть; МИТРИС; DOCSIS; объединение каналов; метод S-CDMA